Bis(sulfonylimide)ruthenium(VI) Porphyrins: X‐ray Crystal Structure and Mechanism of CH Bond Amination by Density Functional Theory Calculations. Issue 34 (1st July 2013) - Guo, Zhen; Guan, Xiangguo; Huang, Jie‐Sheng; Tsui, Wai‐Man; Lin, Zhenyang; Che, Chi‐Ming
Abstract The X‐ray crystal structure of [RuVI(NMs)2(tmp)] (Ms=SO2‐ p‐MeOC6H4; tmp=5, 10, 15, 20‐tetramesitylporphyrinato(2−)), a metal sulfonylimide complex that can undergo alkene aziridination and CH bond amination reactions, shows a RuN distance of 1.79(3) Å and Ru‐N‐S angle of 162.5(3)°. Density functional theory (DFT) calculations on the electronic structures of [RuVI(NMs)2(tmp)] and model complex [RuVI(NMs)2(por0)] (por0=unsubstituted porphyrinato(2−)) using the M06L functional gave results in agreement with experimental observations. For the amination of ethylbenzene by the singlet ground state of [RuVI(NMs)2(por0)], DFT calculations using the M06L functional revealed an effectively concerted pathway involving rate‐limiting hydrogen atom abstraction without a distinct radical rebound step. The substituent effect on the amination reactivity of ethylbenzene by [RuVI(NX)2(por0)] (X=SO2‐p‐YC6H4 with Y=MeO, Me, H, Cl, NO2) was examined. Electron‐withdrawing Y groups lower the energy of the LUMOs of [RuVI(NX)2(por0)], thus facilitating their interaction with the low‐lying HOMO of the ethylbenzene CH bond and hence increasing the reactivity of [RuVI(NX)2(por0)]. DFT calculations on the amination/aziridination reactions of [RuVI(NSO2C6H5)2(por0)] with pent‐4‐enal, an aldehyde substrate bearing acyl, homoallylic, and allylic CH bonds and a CC bond, revealed a lower reaction barrier for the amination of the acyl CH bond than for both the amination of the other CH bonds and aziridination of the CC bond in this substrate.